2015
DOI: 10.1007/s00709-015-0836-z
|View full text |Cite
|
Sign up to set email alerts
|

Fruit ripening mutants reveal cell metabolism and redox state during ripening

Abstract: Ripening which leads to fruit senescence is an inimitable process characterized by vivid changes in color, texture, flavor, and aroma of the fleshy fruits. Our understanding of the mechanisms underlying the regulation of fruit ripening and senescence is far from complete. Molecular and biochemical studies on tomato (Solanum lycopersicum) ripening mutants such as ripening inhibitor (rin), nonripening (nor), and never ripe (Nr) have been useful in our understanding of fruit development and ripening. The MADS-box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 83 publications
(97 reference statements)
7
69
1
1
Order By: Relevance
“…It is well-documented that the expression of genes related to stress responses, primary and secondary metabolism, cell wall metabolism, and hormonal metabolism contribute to fruit ripening process (Shi et al, 2014; Kumar et al, 2015). Previous studies have suggested that ALA enhanced fruit maturation with a promotion of many ripening-related biological events (Watanabe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that the expression of genes related to stress responses, primary and secondary metabolism, cell wall metabolism, and hormonal metabolism contribute to fruit ripening process (Shi et al, 2014; Kumar et al, 2015). Previous studies have suggested that ALA enhanced fruit maturation with a promotion of many ripening-related biological events (Watanabe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 levels increase in the berry skin of grape (Vitis vinifera 'Pinot Noir') at the onset of ripening (veraison), when the most crucial events during berry ripening occur, including the change in color of the skin (Pilati et al, 2014). Studies on tomatoes also have revealed an elevation in H 2 O 2 levels during changes in color of the skin (Jimenez et al, 2002;Kumar et al, 2016). It appears, therefore, that color break during ripening is associated with increased oxidative stress in ripening fruits that is linked to a respiratory burst in the mitochondria and enhanced ROS production during chromoplast generation, which is essential for carotenoid production (Bouvier et al, 1998).…”
Section: Photooxidative Stress In Leaves Flowers and Fruitsmentioning
confidence: 99%
“…A group of genes associated with cellular oxidation and peroxidation processes, including several peroxidases ( Solyc01g006300 , Solyc03g080150 , Solyc06g076630 ), were lower expressed in AtJUB1-OX fruits. Peroxidases are considered to affect fruit softening and ripening (Kumar et al, 2016). Expression of Solyc12g005350 , encoding dihydroflavonol-4-reductase, a key gene in anthocyanin biosynthesis (Holton and Cornish, 1995), is slightly decreased in AtJUB1-OX .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from ACS and ACO , a PECTIN ESTERASE gene ( Solyc06g051960 ) is repressed in AtJUB1-OX fruits compared to wild type; similarly, several pectin esterase encoding genes are repressed in the rin mutant during fruit ripening (Kumar et al, 2016). The absence of the AtJUB1 binding site in the promoters of the ripening-related genes, however, indicates indirect regulation by AtJUB1; the details of the mechanisms that underlie this regulation are currently unknown.…”
Section: Discussionmentioning
confidence: 99%